Comparison of Style and Stylistic Debates - Hussain, Azaadar (sourcecoder, 2024)
In modern Urdu criticism, a trend of stylistic criticism has been seen after linguistics. The scientific study of language is called linguistics whereas the scientific study of style is called stylistics. However, the new student of literature is unable to distinguish between style and stylistic, often moving to style discussion with a focus on stylistic study or analyzing style with a view to stylistic evaluation of a work of art. In this essay, an attempt is made to present the discussions of style and stylistics in such a way that it is easy for the student of literature to distinguish between the two. Style looks at the merits or demerits of many aspects of a work, while stylistics only looks at the use of language and its structure in literature. The main sources of style are author, environment, thought, language and reader, while the source of stylistics is linguistics. There are three main branches of linguistics (historical, descriptive, and applied). Stylistics is studied under Applied Linguistics.